Performance of Wavelet-based Multiresolution Motion Estimation for Inbetweeningin Old Animated Films - Dwi Ratna Sulistyaningrum; Mochamad Hariadi; Mauridhi Hery Purnomo (LPPM ITB, 2012)
This paper investigates the performance of wavelet-based multiresolution motion estimation (MRME) for inbetweening in old animated films using three different MRME schemes. The three schemes are: coarse-to fine with a wavelet-based MRME, one of Zhang's MRMEs, and an MRME in the spatial domain. In order to make a performance comparison of these MRME schemes, two video sequences were used for a simulation. The experimental results show that the coarse-to-fine method performed better than Zhang's MRME and the MRME in the spatial domain. The evaluation results on block size 9x9 indicate that the coarse-to-fine method had an average peak signal-to-noise ratio (PSNR) of 23.48 dB for the first sequence and 29.84 for the second sequence.